Chemical composition of the essential oil of Pogostemon auricularius (L.) Hassk. from Vietnam - Thai, Tran Huy; Hung, Nguyen Quang; Minh, Do Thi; Hong, Phung Tuyet (Academia Journal of Biology, 2014)
Pogostemon auricularius (L.) Hassk. (Lamiaceae) is an erect or procumbent, strongly smelling annual herb, 40-100 cm tall. Stem simple or laxly branched, weak, bluntly 4-angular, pubescent with spread hairs. Leaves decussate, elliptical to oval, 4-6 ´ 2-3 cm; base cuneate; apex acute; margin uregularly surate, flowers and fruits throughout the year. This plant distributes in many provinces of Vietnam (Sonla, Laichau, Laocai, Caobang, Hagiang, Langson, Phutho, Thuathien-Hue, Gialai, Kontum, Ninhthuan, Kiengiang provinces) The essential oil yield of the above ground part of this plant was at 0.13 percent by air-dry material. This essential oil was analysed by GC/MS and its 26 constituents were identified. The main contituents of this oil were: 1h-cyclopropa (a) naphthalen, 1a.2.3.5.6.7.7a octahydrro - 1.1.7.7a.7b tetramethyl (7.30%); b-panasinsen (41.72%), a- panasisen (11.96%).